DNA sequencing and bar-coding using solid-state nanopores - Atas, Evrim (2012)
Nanopores have emerged as a prominent single-molecule analytic tool with particular promise for genomic applications. In this review, we discuss two potential applications of the nanopore sensors: First, we present a nanopore-based single-molecule DNA sequencing method that utilizes optical detection for massively parallel throughput. Second, we describe a method by which nanopores can be used as single-molecule genotyping tools. For DNA sequencing, the distinction among the four types of DNA nucleobases is achieved by employing a biochemical procedure for DNA expansion. In this approach, each nucleobase in each DNA strand is converted into one of four predefined unique 16-mers in a process that preserves the nucleobase sequence. The resulting converted strands are then hybridized to a library of four molecular beacons, each carrying a unique fluorophore tag, that are perfect complements to the 16-mers used for conversion. Solid-state nanopores are then used to sequentially remove these beacons, one after the other, leading to a series of photon bursts in four colors that can be optically detected. Single-molecule genotyping is achieved by tagging the DNA fragments with γ-modified synthetic peptide nucleic acid probes coupled to an electronic characterization of the complexes using solid-state nanopores. This method can be used to identify and differentiate genes with a high level of sequence similarity at the single-molecule level, but different pathology or response to treatment. We will illustrate this method by differentiating the pol gene for two highly similar human immunodeficiency virus subtypes, paving the way for a novel diagnostics platform for viral classification.